A novel digital biomarker of sarcopenia in frail elderly: New combination of gait parameters under dual-task walking - Zhou, Zheping; Huang, Yulun; Wang, Jing; Su, Huan; Tang, Haiying; Wang, Yueju (Frontiers in Aging Neuroscience, 2023)
Frailty caused by deterioration in multiple physiological systems has led to a significant increase in adverse events such as falls, disability and death in frail older people. Similar to frailty, sarcopenia, defined as loss of skeletal muscle mass and strength, is tightly related to mobility disorders, falls and fractures. With population ageing, co-occurrences of frailty and sarcopenia are increasingly common in the elderly, which are more deleterious for the health and independence of older adults. But the high similarity and overlap between the frailty and sarcopenia increase the difficulty of early. The results of this study show that gait speed and turn duration under dual task are good predictors of sarcopenia in frail elderly and turn duration (DT) has a better predictive ability. The gait speed (DT) combined with turn duration (DT) is a potential gait digital Biomarker of sarcopenia in the frail elderly. Dual-task gait assessment and detailed gait indexes provide important value for identification of sarcopenia in frail elderly people.